Neuroprotective Effect of Low-Intensity Transcranial Ultrasound Stimulation in Moderate Traumatic Brain Injury Rats - Zheng, Tao; Du, Juan; Yuan, Yi; Wu, Shuo; Jin, Yinglan; Wang, Zhanqiu; Liu, Defeng; Shi, Qinglei; Wang, Xiaohan; Liu, Lanxiang (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI) is a kind of severe brain injury characterized with a high incidence rate and a high disability rate. Low-intensity transcranial ultrasound stimulation (LITUS) is a promising neuroprotective method for improving the functional prognosis of TBI. The fractional anisotropy (FA) value and mean diffusivity (MD) value can be sensitive to abnormal brain structure and function and can thus be used to evaluate the effect of LITUS on TBI. Our purpose was to evaluate the therapeutic effect of LITUS in a moderate TBI rat model with FA and MD values. For our method, we used 45 male Sprague Dawley rats (15 sham normal, 15 TBI, and 15 LITUS treatment rats). We used single-shot spin echo echo-planar imaging sequences at 3.0T to obtain the DTI parameters. Parameters of FA and MD on the treated side of the injury cortex were measured to evaluate the therapeutic effect of LITUS in a TBI rat model. For FA and MD values, groups were compared by using a two-way analysis of variance for repeated measures, and this was followed by Tukey’s post hoc test. Differences were considered significant at P < 0.05. The results were that the FA value in the LITUS treatment group at 1 day after TBI was significantly higher than that in the control group (adjusted P = 0.0422) and significantly lower than that in the TBI group at 14, 21, and 35 days after TBI (adjusted P = 0.0015, 0.0064, and 0.0173, respectively). At the end of the scan time point, the differences between the two groups were not significant (adjusted P = 0.3242). The MD values in the LITUS treatment group were significantly higher in the early stage than that in the TBI group (adjusted P = 0.0167) and significantly lower at the following time points than in the TBI group. In conclusion, daily treatment with LITUS for 10 min effectively improved the brain damage in the Controlled Cortical Impact (CCI)-caused TBI model. FA and MD values can serve as evaluation indicators for the neuro-protective effect of LITUS.